BRICSAM and the non-WTO - Agata Antkiewicz; John Whalley (Center for Economic Studies and ifo Institute (CESifo), 2005)
We discuss recent regional trade and economic partnership agreements involving the large population rapidly growing economies (Brazil, Russia, China, India, South Africa, ASEAN, Mexico) who (with the exception of Mexico) are also outside of the OECD. Perhaps 50 out of 300 that exist worldwide now involve BRICSAM countries and most are recently concluded and to be implemented over the next few years. Along with extensive bilateral investment treaties, mutual recognition agreements, and other country (or region) to country arrangement they are part of what we term the non-WTO. We are able to find little literature on these agreements, and our aim is to document and characterize, as much as analyze possible impacts. We note the sharp variation both across countries in the form that agreements take and also across agreements for individual countries. Agreements differ in specificity, coverage and content. In some treaties there are detailed and specific commitments, but these also coexist with seemingly vague commitments and (at times) opaque dispute settlement and enforcement. Whether these represent a partial replacement of WTO process for new negotiated reciprocity-based global trade liberalization over the next decade or so, or largely represent diplomatic protocol alongside significant WTO disciplines is the issue we discuss.
Keywords: F00; F02; F15; 330; Internationale Wirtschaftsbeziehungen; Handelsregionalismus; WTO-Regeln; Welt; Schwellenländer